Use of turmeric (Curcuma longa) on the performance and some physiological traits on the broiler diets - Abd Al-Jaleel, Raghdad A. (The Iraqi Journal of Veterinary Medicine, 2012)
This study was conducted at the poultry farm ,Veterinary Public Health .,College of Veterinary Medicine, to study the effect of Tumeric (Curcuma longa) on broiler performance and some physiological traits .Two hundred fifty day-old (Rose308) broiler chicks were all located randomly to five treatments from 1-42 days of age, with tow replicate pens (25 birds /pen) per treatment .Chicks were fed the following :- Diet (1)Using basal diet free from herbal plants kept as control , Diet (2) Basal diet + 0.25% of Curcuma longa (250 gm/100kg of feed) Diet (3) Basal diet + 0.50% of Curcuma longa (500 gm/100kg of feed ).Diet (4) Basal diet + 1% 0f Curcuma longa (1000 gm/100kg of feed ).Diet (5) Basal diet plus 1.5 % of Curcuma longa (1500 gm/100kg of feed ).Results revealed that the inclusion of turmeric at the levels of 0.50% in the diets improved body weight ,feed conversion ratio ,there were a significant difference in feed consumption . At the same time there was no significant difference for edible parts, were as found significant difference (P˂ 0.05) for dressing percent for all treatments treat with compare for control group . At the same time there was no significant difference in PCV, RBC, Hb, WBC while there was significant difference in H/L ratio, Albumin and globulin.